2013
DOI: 10.1096/fj.12-224030
|View full text |Cite
|
Sign up to set email alerts
|

A copper sulfate and hydroxylysine treatment regimen for enhancing collagen cross‐linking and biomechanical properties in engineered neocartilage

Abstract: The objective of this study was to improve the biomechanical properties of engineered neotissues through promoting the development of collagen cross-links. It was hypothesized that supplementing medium with copper sulfate and the amino acid hydroxylysine would enhance the activity of lysyl oxidase enzyme to form collagen cross-links, increasing the strength and integrity of the neotissue. Neocartilage constructs were generated using a scaffoldless, self-assembling process and treated with copper sulfate and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 47 publications
2
84
0
1
Order By: Relevance
“…Different mechanical and biochemical stimuli can be combined to enhance the functional properties of the engineered tissue on par with native tissue values. 23,27,40,41 In this study the native tibial plafond exhibited significantly better properties in comparison with all other locations of the ankle joint. The measured differences of tibial plafond articular cartilage were also mirrored in the biomechanical and biochemical properties of neocartilage constructs generated using tibial plafond cells.…”
Section: Disparity In Articulating Surfaces Of Anklementioning
confidence: 55%
See 1 more Smart Citation
“…Different mechanical and biochemical stimuli can be combined to enhance the functional properties of the engineered tissue on par with native tissue values. 23,27,40,41 In this study the native tibial plafond exhibited significantly better properties in comparison with all other locations of the ankle joint. The measured differences of tibial plafond articular cartilage were also mirrored in the biomechanical and biochemical properties of neocartilage constructs generated using tibial plafond cells.…”
Section: Disparity In Articulating Surfaces Of Anklementioning
confidence: 55%
“…Next, samples were suspended in 50 mL of 10-mmol/L pyridoxine and 2.4-mmol/L homoarginine and then diluted 5Â in 0.5% heptafluorobutyric acid in 10% acetonitrile. For highperformance liquid chromatography, 10 mL of each sample was used as previously described, 27 by use of pyridinoline standards (Quidel, San Diego, CA), to quantify the cross-link content.…”
Section: High-performance Liquid Chromatographymentioning
confidence: 99%
“…[46][47][48] Further, treatment of cell-seeded collagen gels with sodium azide, an ATP inhibitor, or cytochalasin D, a cytoskeletal inhibitor, has been found to inhibit such matrix reorganization following mechanical stimulation. 49,50 Previous work has also correlated increased biomechanical properties in engineered neotissues with increased crosslinks, 38,51 suggesting that the greater functional properties in the middle zone of 10-g-loaded constructs are likely related to the increased crosslink content in this region. Such work indicates that cells, in response to a mechanical input, generate intrinsic traction forces to align compact, and crosslink collagen fibers such that they counter the newly loaded environment.…”
Section: Discussionmentioning
confidence: 97%
“…55,56 Instead, it is now shown that a highly complex and integrated relationship appears to exist that connects not only overall matrix composition, but also its architecture with the functionality of both native and engineered cartilaginous tissues. 34,38,40,[57][58][59] Gaining a better understanding of the intricate relationship between structure and function in engineered tissues should be the focus of future studies to aid in advancing tissue engineering endeavors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation